Hexavalent vaccines: increasing options for policy-makers and providers. A review of the data supporting interchangeability (substitution with vaccines containing fewer antigens) and mixed schedules from the same manufacturer. (3rd June 2018) - Dolhain, Jan; Janssens, Winnie; Mesaros, Narcisa; Hanssens, Linda; Fierens, Frederik
ABSTRACT: Introduction : Combination vaccines improve vaccine uptake and open the infant immunization space for additional vaccines. Hexavalent vaccines have been marketed since 2000. Infanrix hexa (combined diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliovirus- Haemophilus influenzae type b conjugate vaccine, DTPa-HBV-IPV/Hib, GSK) is longest on the market, providing 16 years post-marketing experience. Each DTPa-HBV-IPV/Hib vaccine component is licensed alone and/or in smaller combination vaccines. Programmatic considerations sometimes require an interchange between vaccines due to unavailability, program change or mixed schedules (when the number of required antigens differs across scheduled primary vaccination visits). Areas covered : Immunogenicity and safety data from 11 GSK-sponsored clinical trials support the interchangeability of DTPa-HBV-IPV/Hib within the same vaccines family, and use of DTPa-HBV-IPV/Hib in mixed primary vaccination schedules. Expert commentary : Data show acceptability of interchange of DTPa-HBV-IPV/Hib with other products within the same vaccines family and its use in mixed immunization schedules. This aligns with WHO recommendations that vaccines of the same family from the same manufacturer be used to complete the infant vaccination schedule. Interchangeability and suitability for use in mixed schedules is of interest for policy-makers/providers in the framework of vaccination recommendations as it provides flexibility. Given the complexity of larger combination vaccines, interchangeability or sequential use needs careful assessment.